Plagiarism: A Threat To The Creative Industry Of Handmade Regional Batik Motifs In Indonesia - I Nyoman Lodra; I Nengah Mariasa (Institut Seni Indonesia Denpasar, 2018)
Developments in the creative industry of handmade batik in Indonesia have helped culvating Small and Medium Enterprises (SMEs) in regions such as Klampar village in Pemekasan, Madura, East Java. Efforts to preserve the sustainability of these SMEs need to be balanced by protecting handmade batik motifs with copyright in order to save this intellectual wealth from plagiarism. This study focuses on: 1) efforts to ensure that plagiarism does not occur and does not threaten the creative industry in Indonesia; 2) benefits from the protection of handmade batik motifs for the creative industry in Indonesia. The research goal is to protect handmade batik motifs from plagiarism and discover the benefits of this protection on the creative industry in Indonesia. A descriptive qualitative research method is used with an empirical juridical approach. The data were obtained from SME administrators and public figures in the Madura community. The data was collected from observation, interviews, and documents, analyzed with a method of triangulation, and compiled systematically. The research findings show that the protection of the database of handmade batik motifs can be implemented through E-Copyright which also supports the sustainability of the creative industry of handmade batik in Indonesia.Perkembangan industri kreatif batik tulis di Indonesia mampu menumbuhkembangkan usaha kecil dan menengah (UKM) di daerah seperti halnya di Desa Klampar, Pemekasan, Madura Jawa Timur. Kebangkitan UKM tersebut seharusnya di imbangi dengan perlindungan Hak Kekayaan Intelektual atau disebut HKI bidang Hak Cipta sebagai upaya penyelamatan motif batik tulis dari plagiarisme (plagiator) namun hal itu tidak dilakukan. Penelitian ini penting dilakukan dengan fokus: 1) bagaimana upaya agar tidak terjadi plagiarisme dan tidak menjadi aacaman industri kreatif di Indonesia? 2) apa manfaat perlindungan motif batik tulis untuk industri kreatif di Indonesia?. Tujuan penelitian: memproteksi motif batik tulis agar tidak terjadi plagiarisme dan mengetahui manfaat perlindungan untuk industri kreatif di Indonesia. Metode penelitian deskritif kualitatif dengan pendekatan yuridis imperis. Sumber data diproleh dari pengelola UKM, tokoh masyarakar Madura. Data terkumpul melaluiÂ obsevasi, wawancara, dokumen kemudian di analisis dengan trianggulasi dan disusun secara sistimatis. Temuan penelitian: dapat perlindungan Hak Cipta pada database motif batik tulis dan penyelamatan industri kreatif batik tulis dari plagiarisme di Indonesia.Â